Pollutant removal from agricultural drainage water using a novel double-layer ditch with biofilm carriers. (August 2020) - Zhao, Yonggui; Shu, Xiangdi; Tu, Qi; Yang, Yuejiao; Liu, Chang'e; Fu, Denggao; Li, Wei; Duan, Changqun
Graphical abstract: Highlights: Novel double-layer ditch performs better than single-layer ditch in pollutant removal. High amount and CNP contents of biofilm are favourable to pollutant removal. Bacterial diversity of biofilm remains stable but relative abundance varies greatly. The application of biofilm carriers in double-layer ditch is feasible and efficient. Abstract: Agricultural drainage ditches can prevent flooding and mitigate agricultural pollution; however, the performance is unsatisfactory in plateau areas like the Dianchi Lake basin. Thus, a novel double-layer ditch system (DDS) with a fibrous packing as biofilm carriers was developed to form the carrier-attached biofilms and enhance the pollutant removal. The results indicated the DDS performed better than a single-layer ditch system, and annual average removal efficiencies of TN, NO3 − -N, NH4 + -N, TP, COD and SS were 18.61%, 17.13%, 7.74%, 11.90%, 11.95% and 23.71%, respectively. High amount and carbon, nitrogen and phosphorus contents of biofilms are favourable to pollutant removal by DDS. Although bacterial diversity of biofilms remained relatively stable throughout the year, the relative abundance of dominant assemblages varied greatly. Denitrifying microorganisms affiliated with Bacteroidetes might contribute to effective NO3 − -N reduction. This study demonstrates DDS performed well and provides a novel method for application of biofilm carriers in drainage ditches.